Design of a bipedal robot for rapid acceleration and braking manoeuvres - Blom, Alexander Francois (Department of Electrical Engineering, 2020)
Animals in nature are capable of performing rapid acceleration and braking manoeuvres with ease. However, they have been avoided by researchers due to the complexities of this motion. To investigate and test novel control schemes for such motions, a highly agile mechanical robot is required. The aim of this dissertation was to build a bipedal robot to perform optimal rapid acceleration manoeuvres. This focused on investigating existing robots and using the information therein to design, build and test a new bipedal robot with high agility. The author performed a vigorous investigation into existing actuator schemes and leg topologies that promote agility, balancing the numerous trade-off’s such as mass-specific force and proprioception. This led to the selection of a Quasi-Direct Drive transmission with a scissor linkage leg. Legged robots were generally designed around some known motion [1]. However, selecting suitable mechanical parameters for agile motions with a lack of relevant research was challenging. Trajectory optimisation methods were used to generate unique acceleration motions for bipedal models, aiding in the selection of several physical parameters. With this, a detailed design of Baleka was created, prioritising desirable characteristic for rapid motions. Through several design iterations, the outcome was a fully assembled light weight bipedal robot. All the supporting systems required to operate Baleka were designed and set up, including the Real-time control system, relevant sensors and a boom support to keep it planar. A known metric, vertical agility [2], was used to compare Baleka’s agility to existing robots. Furthermore, a Raibert Controller [3] was also tested on the platform to investigate the robustness of the design. Baleka was found to be the most agile bipedal robot, exceeding the agility of humans. It was able to hop higher than all other robots, verifying it’s suitability for rapid acceleration manoeuvres. However, from the repetitive hopping experiments and high impact forces, slight plastic deformation was witnessed in the gearbox drive shafts.